ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN (Studi pada pengguna Smartphone ASUS Zenfone Max Pro (M2) ZB631KL di Kota Semarang) - Albertus Agung Prasetyono; Idris Idris (Diponegoro Journal of Management, 2022)
The smartphone enlargement in Indonesia is growing too fast nowadays, accompanied by the changes in lifestyle and consumer behavior which are starting to switch from cellphones to smartphones. Various smartphone brands compete to gain market share supported by qualified product quality and affordable prices. Brands requires the right marketing strategy, in order to attract the purchasing decision of the people. This study aims to analyze the factors that affect the purchasing decision of ASUS smartphones. The populations used in this research are users who are currently or have used the ASUS Zenfone Max Pro (M2) ZB631KL smartphone. The number of samples used is 110 respondents. The analysis technique used is Structural Equation Modeling by using AMOS 23.0 analysis tool. The results showed that product quality, price and brand image have a positive and significant effect on purchase intention, and product quality, price, brand image and purchase intention have a positive and significant effect on pruchase decision.